The Role of Emotional Branding in Echancing Customer Satisfaction and Loyalty - Wardana, Wikrama (Dinasti Review, 2025)
The increasing competitiveness of global and regional markets has necessitated a shift from traditional, functional branding toward strategies that foster emotional connections with consumers. This study aims to examine the influence of emotional branding on customer satisfaction and customer loyalty, with customer satisfaction analyzed as a mediating variable. A quantitative approach was adopted, and data were collected from 250 consumers in Indonesia who have engaged with brands employing emotional branding strategies. Using partial least squares structural equation modeling (PLS-SEM), the findings reveal that emotional branding has a significant positive effect on both customer satisfaction and customer loyalty. Furthermore, customer satisfaction significantly mediates the relationship between emotional branding and customer loyalty. The results suggest that emotional branding not only directly fosters loyalty but also enhances satisfaction, which in turn leads to stronger and more sustainable loyalty. The study contributes to the emotional branding literature by validating these relationships in the emerging market context of Indonesia. It also provides managerial insights, emphasizing the need for brands to ensure that emotional engagement is consistently supported by satisfying customer experiences to optimize loyalty outcomes.